The Effectiveness of Phosphate Solubilizing Rhizobacteria on The Growth and Yield of Several Soybean Varieties on Ultisol Soils - Diyanti, Afri R.; Utama, M Z.H.; Ernita, Milda (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2020)
ABSTRACH This study aims to obtain the interaction of rhizobacteria and soybean varieties, types of rizobacteria that effectively dissolve phosphate, varieties that are able to grow well on ultisol soils. The research is rizobacterial isolation and rizobacteria selection. Observations made were bacterial isolation, identification of morphological and physiological rhizobacteria (gram reactions, hypersensitive reactions, as phosphate solvents and germination test and rhizobacteria test of phosphate solvents by inplanta. The results showed that rizobacteria isolates from ultisol soil of chilli plants, eggplant plants and rice roots obtained 32 isolates. The highest number of isolates were obtained from the ultisol soil of chilli plants namely 18 isolates. The color of the rizobacteria isolate colony was obtained by 27 cream isolates and 5 yellow isolates. The surface of the colony in the chilli ultisol soil consisted of 3 groups namely arising, flat and convex, the surface of the colony arising obtained 8 isolates, the flat surface obtained 9 isolates and the convex surface obtained 1 isolate. All isolates were gram negative. From 32 rizobacteria isolates, there were 2 isolates which were able to dissolve phosphate, namely RT1 and RC3. In green bean plants with RT1 administration, the seeds weight was 2.76 grams high compared to control and RC3. Key words: Rhizobacteria solvent phosphate RT1, RC3, ultisol, mung bean